Dickkopf-1 negatively regulates the expression of osteoprotegerin, a key osteoclastogenesis inhibitor, by sequestering Lrp6 in primary and metastatic lytic bone lesions. Issue 24 (June 2016) - Wang, Jian-Hang; Zhang, Yuanjin; Li, Hong-Yan; Liu, Yun-Yan; Sun, Tao
Abstract : Abstract: Recently, an inverse role for Wnt signaling in the development of osteoclasts in the bone was demonstrated. In the present study, we examined whether there is a commonality in the mechanism of bone resorption and lysis that occur in a diverse set of bone metastatic lesions, as well as in primary bone lesions. Compared with control bone tissue and bone biopsies from patients with nonmetastatic primary tumors (i.e., breast carcinoma, lung adenocarcinoma, and prostate carcinoma), patients with bone metastatic lesions from the three aforementioned primary tumors, as well as osteolytic lesions obtained from the bone biopsies of patients with multiple myeloma, demonstrated an upregulated expression of the glycoprotein Dickkopf-1 at both the mRNA and protein levels. Additionally, by coimmunoprecipitation, Dickkopf-1 pulled-down low-density lipoprotein receptor-related protein 6 (Lrp6), which is a key downstream effector of the Wnt signaling pathway. The expression of Lrp6 was unaltered in the osteometastatic lesions. This negative regulation was associated with a lowered expression of osteoprotegerin in the osteometastatic lesions, an observation that was previously reported to promote osteoclastogenesis. These findings provide a common mechanism for the inverse relationship between the Wnt signaling pathway and the development of primary or metastatic bone lesions. Pharmacological modulation of the Wnt signaling pathway might benefit the clinical management of primary and metastatic bone lesions.